2021
DOI: 10.1107/s2052252521005613
|View full text |Cite
|
Sign up to set email alerts
|

Conformational flexibility of EptA driven by an interdomain helix provides insights for enzyme–substrate recognition

Abstract: Many pathogenic gram-negative bacteria have developed mechanisms to increase resistance to cationic antimicrobial peptides by modifying the lipid A moiety. One modification is the addition of phosphoethanolamine to lipid A by the enzyme phosphoethanolamine transferase (EptA). Previously we reported the structure of EptA from Neisseria, revealing a two-domain architecture consisting of a periplasmic facing soluble domain and a transmembrane domain, linked together by a bridging helix. Here, the conformational f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…The conformational changes of EptA are governed by a highly conserved domain structure that offers extensive flexibility between the membrane-bound and the periplasmic catalytic domains (Anandan et al, 2017;Anandan and Vrielink, 2020a). Moreover, Anandan et al (Anandan et al, 2021) proposed that the bridging helix acts as a hinge region that enables extensive conformational changes between the two domains, "opening up" the catalytic domain to allow access to the considerably large lipid A substrate. Hence, diversification of Ser 191 and Arg 235 is likely to influence the overall conformational flexibility of the enzyme.…”
Section: Evolution and Diversification Of Mcr Is The Results Of A Mul...mentioning
confidence: 99%
See 1 more Smart Citation
“…The conformational changes of EptA are governed by a highly conserved domain structure that offers extensive flexibility between the membrane-bound and the periplasmic catalytic domains (Anandan et al, 2017;Anandan and Vrielink, 2020a). Moreover, Anandan et al (Anandan et al, 2021) proposed that the bridging helix acts as a hinge region that enables extensive conformational changes between the two domains, "opening up" the catalytic domain to allow access to the considerably large lipid A substrate. Hence, diversification of Ser 191 and Arg 235 is likely to influence the overall conformational flexibility of the enzyme.…”
Section: Evolution and Diversification Of Mcr Is The Results Of A Mul...mentioning
confidence: 99%
“…The AA residues predicted to evolve under positive selection were not part of the active site and the substrate-binding site; however, they are likely to affect enzyme function, such as possible alteration of substrate accessibility, specificity, and enzyme efficacy. For example, we predicted that branch-specific positive selection might be involved in the diversification of Ser 191 and Arg 235 in the interdomain-connecting region, which is relevant, as it has been shown that the conformational flexibility of EptA is essential in enzyme-substrate recognition ( Anandan et al., 2021 ). The conformational changes of EptA are governed by a highly conserved domain structure that offers extensive flexibility between the membrane-bound and the periplasmic catalytic domains ( Anandan et al., 2017 ; Anandan and Vrielink, 2020a ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, we predicted that branch-specific positive selection might be involved in the diversification of Ser 191 and Arg 235 in the interdomain-connecting region. Recently, it has been shown that the conformational flexibility of EptA is essential in enzyme-substrate recognition (Anandan et al, 2021). The conformational changes of EptA are governed by a highly conserved domain structure that offers extensive flexibility between the membrane-bound and the periplasmic catalytic domains (Anandan et al, 2017; Anandan and Vrielink, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The conformational changes of EptA are governed by a highly conserved domain structure that offers extensive flexibility between the membrane-bound and the periplasmic catalytic domains (Anandan et al, 2017; Anandan and Vrielink, 2020). Moreover, Anandan et al (Anandan et al, 2021) proposed that the bridging helix acts as a hinge region that enables extensive conformational changes between the two domains, “opening up” the catalytic domain to allow access to the considerably large lipid A substrate. Hence, diversification of Ser 191 and Arg 235 is likely to influence the overall conformational flexibility of the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation in the PyMOL framework makes it accessible for regular use, even by non-experts. For instance, MPBuilder was used for the interpretation of SAXS data of the phosphoethanolamine enzyme that is active at the lipidic interface, namely lipid A of pathogenic gram-negative bacteria as an antibiotic resistance mechanism [ 55 ].…”
Section: Protein Sequences and Structures Analyses (Pssas)mentioning
confidence: 99%